A STUDY ON THE COMPACTNESS OF SETS - Umar, Terrang, Abubakar; Bwanu, Patience Iliya (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
The general properties of compact sets are looked at in the study such as compactness implies closedness, compactness implies bounded. In order to achieve these we briefly looked at metric spaces, normed vector spaces from which we considered metric that is being induced by a norm. Considered also is the convergence property of some sequences chiefly Cauchy sequence on which the completeness concept of a set consequently continuity and boundedness properties are established and property of a finite dimensional compact sets. Everything looked at is concise.